Bio-inspired citric acid-based bimetallic photocatalyst for nitrogen fixation from air under ambient conditions. (15th March 2023) - Chen, Yutong; Sun, Qiang; Tu, Xuewei; Chen, Liangchen; Han, Weihang; Zhang, Luping; Duan, Xiaofei; Liu, Min; Zheng, Hui
Abstract: Discovery of effective materials for photocatalytic nitrogen fixation under ambient conditions provides new opportunities for sustainable futures. Nitrogenase provides the best example of environmentally friendly nitrogen reduction. Inspired by homocitrate's specific activating effect on nitrogenase, citric acid was used instead of homocitric acid to prepare citric acid-based bimetallic organic frameworks (MOFs). Metals such as cerium and copper as bimetallic centers were coordinated with citric acid to mimic FeMo bimetallic active center in the M cluster. The results show that the morphology, structure and photocatalytic activity of the catalysts has been significantly affected by the amount of citric acid. The molar ratio of total metal to citric acid of 1.5:20 had the best ammonia evolution rate from air at a normal temperature and pressure (NTP), which was as high as 1027.6 μg g −1 h −1 . It was further confirmed by the numerically study of the interactions between light and the synthesized photocatalytic particles, which can be intuitively seen that CeCu@CA-20 can support more surface charges. This work provides an effective strategy for citrate-based MOF photocatalysts and offers a new idea for nitrogenase biomimetics. Graphical abstract: Image 1 Highlights: A series of citric acid (CA)-based bimetallic organic frameworks were designed. The citric acid-based MOF was inspired by homocitrate in FeMo-co of nitrogenase. CA plays a key role in the change of morphology, structure and optical properties. The CeCu@CA-20 yields 1027.6 μg g −1 h −1 NH4 + from air directly. The interactions between light and the photocatalysts have been numerically studied.